Optimization of Electric Vehicle Battery Recycling through Green Chemical Processes and Circular Economy Principles - Yuniansyah Yuniansyah; Suprayuandi Suprayuandi; Evan Apriadi Delatama; Tri Akhayari Romadhon (International Forum of Researchers and Lecturers, 2024)
This study focuses on optimizing electric vehicle (EV) battery recycling through the use of green chemical processes and circular economy principles. The research aims to enhance the recovery of valuable metals lithium, cobalt, and nickel from used lithium-ion batteries (LIBs) in an environmentally sustainable manner. Green solvents were employed as a safer alternative to conventional, toxic chemicals, minimizing hazardous waste emissions and improving the efficiency of the recycling process. Experimental results showed that the green solvent-based process achieved high recovery rates of 90% for cobalt, 87% for nickel, and 85% for lithium, with metal purity levels exceeding 95% for all three metals. The study also examined the scalability of the green solvent method, revealing its potential to offer more sustainable and cost-effective solutions compared to traditional methods, which typically involve high temperatures and toxic chemicals. Despite the promising results, challenges such as solvent recovery and the adaptation of the process for large-scale industrial applications remain. Nonetheless, the study demonstrates that integrating green solvent-based recycling into the global EV supply chain can significantly reduce environmental impacts, conserve resources, and support the transition to a circular economy. The findings highlight the potential of this recycling method to provide a more sustainable and efficient solution for EV battery recycling, ultimately contributing to the development of a more sustainable EV industry.